Genetic algorithm for event scheduling system - Hasan Basari, Abd Samad; Hussin, Burairah; Jalal, Siti Musliza; Mohd Isa, Nabihah (Penerbit Universiti, UTeM, 2010)
UTeM’s Event Alert System (UTeM-EAS) is an improved version of previous Event Alert System in Universiti Teknikal Malaysia Melaka (UTeM) official site that aims to apply Artificial Intelligence (AI) in order to provide its users with events priority. This newer system intend be more user friendly by providing organized management. The improved version is also designed to have the capability of sending Short Message Service (SMS) among UTeM’s staff to notify them of future events. Some researches about another existing Event Alert Sytem are carried to provide more understanding to the system to be developed. UTeM-EAS then is created by exploiting one of AI approach namely Genetic Algorithm (GA) with Crossover Technique. There are four main interfaces that ask for login information, add, edit and view events details. As for the development environment, UTeM-EAS is developed and to run in windows XP with support of Adobe Dreamweaver and MS SQL Server. Ozeki Messager 6 are installed and configured for this system to operate with its SMS function. The functionality, usability and security testing are conducted between UTeM’s staffs and administrators itself to measure the performance and user acceptance of the proposed system. Aside from achieving its development objectives, UTeM-EAS also gain great satisfactions from most of its tested users. The system could be more efficient if password encryption is applied and the system is able to reply the message sent by UTeM’s staff asking for further events details.